Women Making Music in Canada: Issues of Cultural Identity that Influence Compositional Styles and Strategies - Burke, J-M. Nadine (My University, 2003)
It is essential that Canadian ethnic music multiplicities be recognized within intercultural, intracultural and transcultural contexts and to acknowledge that categories of social class, race, ethnoculture and gender are influenced by geographic location, historical location and opportunity. Women musicians, such as Cathy Babyak (On-Yon Taiko), Brenda MacIntyre (Spirit Wind) and Zainab Amadahy (Spirit Wind), inhabit multiple spaces as a result of their historical and political heritage, their familial history and their social and economic environment. Experiencing the music-making of these women, hearing their words and expanding my understanding of their music through emic sources gave me the tools to develop a theoretical approach to articulate their standpoint.
In this thesis, I employ transcultural standpoint and other methodological approaches to understand how these women inhabit multiple spaces. In particular, transcultural standpoint, as a tool, enables me to problematize and explicate everyday life and the influence of music-making in order to determine how Babyak, MacIntyre and Amadahy communicate the social relations that they experience and how the values of their communities and heritages enter into, complement, complicate and shape the structure and organization of their musicmaking. Elements of these value systems are discovered through an analysis of three songs: "Hiryu Sandan Gaeshi," 'co-composed' by On-Yon Taiko, "Love Peace Reflections" by Brenda MacIntyre and "Celebrating Red & Black" by Zainab Amadahy.
Keywords: Music; Music